An Operator Looks Back at 45 Years of Change. Issue 8 (7th October 2021) - Forbes, Steven
Abstract : "Change"—this word defines my 45‐year career in utility operations. Over the years, I've learned that operators must make a conscious effort to understand the patterns and impacts of past practices to be successful in the present and future.